ARAH BARU KEBIJAKAN KURIKULUM MERDEKA BELAJAR DI SEKOLAH DASAR - Ahmad Sahnan; Tri Wibowo (SITTAH: Journal of Primary Education, 2023)
The government has launched an independent learning curriculum complete with its socialization strategy. However, many educational institutions still have difficulty implementing the independent learning curriculum policy. This research aims to analyze the direction of the independent learning curriculum policy for elementary schools. The research method that researchers used was library research. Data collection techniques used documentation methods. Data analysis techniques used content analysis techniques. The data obtained were then analyzed to be presented. This study's results indicate three directions of independent learning curriculum policies at the elementary school level: independent learning, independent innovation, independent self-learning and creative. Applying these three directions in each learning process can facilitate students to have an enjoyable learning experience.